Can public relations put the trust back in organisations? - Venter, Ben-Piet; Van der Merwe, Johann (Department of Communication Science, University of the Free State, 2009)
The last two years have seen top South African and international companies being accused or criticised for activities that do not serve the interests of their stakeholders. A sad result of this and other organisational philandering is that the name of public relations – already tainted – is sullied even more. The ethics of organisational management, the ethical impacts of public relations, and the ethics of public relations practitioners are addressed in this article. In deliberating the sticky ethics issue, the current role of public relations in the organisation as well as public relations education in South Africa are also discussed. It is suggested that the value chain can be used to assist public relations in overcoming its uncertain position in the ethics debacle by firstly placing it firmly in the organisation’s value chain as a support activity alongside those of human resources, firm infrastructure, and technology development; secondly that the placement of public relations as support function in the value chain is a good argument for the allocation to public relations of its rightful place in the organisation’s formal chain of command; and thirdly, given the acceptance that public relations is a support function not only to marketing and sales, but also to inbound logistics, operations, outbound logistics, and service, it becomes necessary to revise the educational curriculum of public relations students.
Keywords: Public relations; Ethics; Ethics of organisational management